Cooking oil-surfactant emulsion in water for harvesting Chlorella vulgaris by sedimentation or flotation - Potocar, Tomas; Leite, Luan de Souza; Daniel, Luiz Antonio; Pivokonsky, Martin; Matoulkova, Dagmar; Branyik, Tomas (Bioresource technology, 2020)
In this study, a novel harvesting emulsion (HEM) consisting of cooking oil in an aqueous solution of cetyltrimethylammonium bromide (CTAB) was tested for the harvesting of a technologically important microalga, Chlorella vulgaris. The influence of HEM dose, biomass and bovine serum albumin (BSA) (model interferer compound) on harvesting efficiency (E) were studied. The HEM E was over 90% at pH 10 (0.33% (v/v) cooking oil, 6.7 mg/L of CTAB) and 12 (0.13% (v/v) cooking oil, 2.7 mg/L of CTAB). Harvesting efficiencies at pH 4 and 7 were < 73.5% due to the absence of precipitate formation. Bovine serum albumin (10 mg/L) increased the HEM dose necessary to achieve E ˃ 90% by 1.2 (pH 10), and 3 fold (pH 12). By manipulating the dose of HEM and pH, the method of harvesting (flocculation/sedimentation or flotation) was adjustable depending on the technological requirements.
Keywords: Cooking; Biomass; Flocculation; biomasa; vaření; Microalgae; voda; povrchově aktivní látky; mikrořasy; flokulace; Water; Surface-Active Agents; Chlorella vulgaris